2009
DOI: 10.1074/jbc.m109.031344
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Core Mutations Associated with Cataract Development in Mice Destabilize Human γD-Crystallin

Abstract: The human eye lens is composed of fiber cells packed with crystallins up to 450 mg/ml. Human γD-crystallin (HγD-Crys) is a monomeric, two-domain protein of the lens central nucleus. Both domains of this long lived protein have double Greek key β-sheet folds with well packed hydrophobic cores. Three mutations resulting in amino acid substitutions in the γ-crystallin buried cores (two in the N-terminal domain (N-td) and one in the C-terminal domain (C-td)) cause early onset cataract in mice, presumably an aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
81
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 68 publications
13
81
0
Order By: Relevance
“…After irradiation, the intensity of the Trp-42 H⑀1 resonance was reduced by 50%, that of Trp-68 was reduced by 37%, whereas that of Trp-156 was only decreased by 5% (Fig. 7A) 15 N HSQC spectrum after irradiation, indicating that new protein species had appeared. We estimated which parts (amino acids) of HGD experienced damage by measuring the intensities of resonances that were associated with undamaged protein over the time course of the irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After irradiation, the intensity of the Trp-42 H⑀1 resonance was reduced by 50%, that of Trp-68 was reduced by 37%, whereas that of Trp-156 was only decreased by 5% (Fig. 7A) 15 N HSQC spectrum after irradiation, indicating that new protein species had appeared. We estimated which parts (amino acids) of HGD experienced damage by measuring the intensities of resonances that were associated with undamaged protein over the time course of the irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm that the small resonances do not arise from an unrelated chemical species, but belong to the partially folded minor I-state that can exchange with the major N-state, we also performed H/D exchange experiments for 15 N HSQC spectra were recorded as a function of time. In the folded state, slow exchange of amide hydrogens with deuterons occurs (43), whereas in the unfolded state, exchange is fast.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also find that, upon N-td unfolding the C-td undergoes a net approximatley 23% increase in solvent-exposed surface area (probed using a sphere of 1.4 Å) from the crystal structure. Recent experiments also suggested that a partial unfolding of the C-td is required for aggregation, further demonstrating the structural similarity between the simulated folding intermediate and the experimentally detected aggregation-prone species (23). To map this structural change of the C-td at the residue level, the root-mean-square fluctuation (RMSF) and the %SASA increase in the I2 ensemble as well as the hydrophobicity of each residue within the C-td were calculated (Fig.…”
Section: Resultsmentioning
confidence: 99%